Pengaruh Motivasi, Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Pegawai Sekretariat DPRD Provinsi Sulawesi Selatan - Andi Nila Ratna Sari; A.Niniek F. Lantara; Ackhriansyah Ahmad Gani (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Abstract This study employed a quantitative approach using a survey method. The population of this research consisted of all civil servants at the Secretariat of the Regional House of Representatives (DPRD) of South Sulawesi Province, totaling ninety-four employees. The sampling technique used was Simple Random Sampling, in which each member of the population had an equal opportunity to be selected as a research respondent. Based on this technique, a sample of eighty employees was obtained. Data were collected through the distribution of questionnaires to respondents, while the data analysis technique used was multiple linear regression analysis, preceded by classical assumption tests to ensure the feasibility of the research model. The results of the study indicate that work motivation has a positive and significant effect on employee performance. This finding shows that the higher the level of work motivation possessed by employees, the better the performance produced. Leadership does not show a significant effect on employee performance, indicating that in bureaucratic organizations employee performance tends to be more influenced by formal work systems and clearly defined job responsibilities. Meanwhile, the work environment shows a positive and significant effect on employee performance, meaning that a conducive work environment, in terms of work facilities, comfort, and interpersonal relationships among employees, can enhance the effectiveness and productivity of employee performance. Simultaneously, work motivation, leadership, and the work environment influence employee performance. This indicates that improving employee performance is the result of the interaction between individual psychological factors, managerial factors within the organization, and work environment conditions that support the implementation of employee duties. Therefore, organizations are expected to enhance employee work motivation and create a more conducive work environment in order to support sustainable improvements in employee performance. Keywords: Work Motivation, Leadership, Work Environment, Employee Performance